Pelaksanaan Kegiatan Ekstrakurikuler Paduan Suara Di SMPN 37 Pekanbaru Tahun Ajaran 2025/2026 - Andika Saputra; Nurmalinda (Advances In Education Journal, 2026)
This research aimed to determine the implementation of choir extracurricular activities at SMP Negeri 37 Pekanbaru in the 2025/2026 academic year, which was motivated by the importance of extracurricular activities as a means of developing students’ talents, interests, creativity, and abilities in non-academic fields, especially music arts. This research used a descriptive method with a qualitative approach, and the research subjects consisted of the choir extracurricular instructor, choir students, and the school staff. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis techniques were conducted through data collection, data reduction, data presentation, and conclusion drawing. The results of the research showed that the implementation of choir extracurricular activities at SMP Negeri 37 Pekanbaru had been carried out quite well and conducted regularly according to the predetermined schedule. The training activities included vocal warm-ups, breathing exercises, articulation, intonation, voice division, and harmony practice. This activity gave positive impacts on students such as improving singing ability, self-confidence, discipline, responsibility, and cooperation. In its implementation, there were still several obstacles such as limited facilities and infrastructure as well as inconsistent attendance of some students during practice sessions, however, the choir extracurricular activity was still able to run well because of support from the school, instructor, and students’ enthusiasm in participating in the training activities.